2021
DOI: 10.1519/jsc.0000000000002770
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Physical Fitness Parameters Between Professional and Amateur Greek Soccer Players During the Transition Period

Abstract: Bekris, E, Pidoulas, G, Pidoulas, P, Gissis, I, Katis, A, and Komsis, S. Examination of physical fitness parameters between professional and amateur Greek soccer players during the transition period. J Strength Cond Res 35(3): 776–781, 2021—The aim of the study was to compare physical fitness parameters between professional and amateur soccer players of different levels. The sample consisted of 381 soccer players divided in 4 experimental groups: first division professional players (n = 115), second division p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…Studies have measured countermovement jump height in soccer young players showing means around 38 cm [21], all of them higher than the value of this study. Eliakim et al [22] found that players who got injured during the season, jumped 36.8 cm in the preseason screening test.…”
Section: Strengthcontrasting
confidence: 83%
“…Studies have measured countermovement jump height in soccer young players showing means around 38 cm [21], all of them higher than the value of this study. Eliakim et al [22] found that players who got injured during the season, jumped 36.8 cm in the preseason screening test.…”
Section: Strengthcontrasting
confidence: 83%
“…In addition, VO 2 max has been shown to contribute to a competitive ranking [6]. Nonetheless, values presented by Bekris, et al [8], whose cohort more closely matches that of this study, reveal mean values of 57.41 ml/kg/min in D1 players, with VO 2 max values signifi cantly decreasing between professional divisions. However, such data needs to be carefully evaluated before comparisons between studies are made, due to the diff erent criteria used to distinguish the subjects (i.e., elite, sub-elite, non-elite, professional, semi-professional, amateurs etc.)…”
Section: Introductionsupporting
confidence: 71%
“…Elite soccer players (D1) competing in the Greek championship were slightly taller (181 ± 6.5 cm) and heavier (77.7 ± 6.6 kg) compared to players in the lower divisions, supported by fi ndings in a study by Bekris, et al [8] who also identifi ed these diff erences. Their anthropometric measures were comparable to those of elite European soccer players, such as Icelandic, Serbian, English Premier League players, Norwegian, Slovak, and Spanish D1 players [2,4].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations